Azak during the Golden Horde Dynastic War (1359–1380) - Maslovskiy Andrey N. (Поволжская археология)
This article deals with the Azak archaeology, concerning the period of the Golden Horde Dynastic War after the Berdibek Khan assassination and before Tokhtamysh Khan came to power (1359–1381). After the crisis and stagnation of the previous period (1343–1359), without a noticeable urban area reduction, during the Great Troubles period there was a decrease in the city area by 4 times. Azak's ties with other regions have fallen to a minimum. At the first stage (before 1369/1370), an increase in prosperity and the flourishing of crafts, in particular pottery, is recorded, which was probably due to a new population influx. The city has not been recovered to its former level. Most of the richest complexes studied in Azak belong to this time. A huge number of copper coins were minted. Traces of local destructions on the city outskirts are also recorded. Then a period of instability begins, as evidenced by the construction of a defensive fosse. During the winter of 1369/1370, dramatic events took place in the city, which led to the appearance of mass sanitary graves and the peripheral areas desolation. This had little effect on the city center. The consequences were delayed in time. After that, the issue of the copper coin is almost completely stopped. This makes it difficult to date the complexes of 1370–1381. It can be stated that there have been no significant changes in the city center, and the same building density has been preserved, but many areas on the periphery of the central district have been abandoned. Tokhtamysh Khan’s rise to power was also accompanied by excesse, as evidenced by the finds of sanitary burial and hoards in Azak and the surrounding area.